TI_GERICHTE 15.2010.55 vom 5. Juli 2010 , Rivendicazione di beni pignorati. Assegnazione del termine per agire giudizialmente - TI Tribunale d'appello (2010)
Rivendicazione di beni pignorati. Assegnazione del termine per agire giudizialmente